Environmental impact assessment theory and practice (London Routledge, 1990)
Provides an authoritative contemporary review of both the science and art of EIA, reflecting concern both with the technical aspects of appraisal and the effects of EIA on the decision-making process.
Book Cover; Title; Contents; Foreword; Acknowledgements; List of Tables; List of Contributors; INTRODUCTION; An introductory guide to EIA; METHODOLOGICAL ASPECTS OF EIA; Scoping methods and baseline studies in EIA; Developments in EIA methods; Uncerta inty in EIA; Environmental impact assessment and risk assessment: learning from each other; EIA in plan making; EFFICACY OF EIA; Monitoring and auditing of impacts; The evaluation of assessment: post-EIS research and process development; Training requirements for environmental impact assessment; APPLICATION OF EIA
Includes bibliographical references and index.
Keywords: Environmental impact analysis